Quantitative cytokine level of TNF-α, IFN-γ, IL-10, TGF-β and circulating Epstein-Barr virus DNA load in individuals with acute Malaria due to P. falciparum or P. vivax or double infection in a Malaria endemic region in Indonesia. - Insani Budiningsih; Yoes Prijatna Dachlan; Usman Hadi; Jaap Michiel Middeldorp (PLoS ONE)
Plasmodium falciparum Malaria and Epstein-Barr Virus (EBV) infection are risk factors in the development of Burkitt's lymphoma. In Indonesia, 100% of the population is persistently infected with EBV early in life and at risk of developing EBV-linked cancers. Currently, 10.7 million people in Indonesia are living in Malaria-endemic areas. This cross-sectional study was initiated to investigate how acute Malaria dysregulates immune control over latent EBV infection. Using blood and plasma samples of 68 patients with acute Malaria and 27 healthy controls, we measured the level of parasitemia for each plasmodium type (P. falciparum, P. vivax, and mixed) by microscopy and rapid test. The level of 4 regulatory cytokines was determined by quantitative ELISA and the level of circulating EBV genome by real-time PCR targeting the single copy EBNA-1 sequence. All Plasmodium-infected cases had high-level parasitemia (>1000 parasites/ul blood) except for one case. EBV-DNA levels were significantly more elevated in P. falciparum and P. vivax infections (P<0.05) compared to controls. EBV-DNA levels were not related to age, gender, Malaria symptoms, or plasmodium type. TNF-α and IL-10 levels were increased in Malaria cases versus controls, but IFN-γ and TGF- β levels were comparable between the groups. Only TNF-α levels in P. falciparum cases showed a clear correlation with elevated EBV DNA levels (R2 = 0.8915). This is the first study addressing the relation between EBV (re)activation and cytokine responses during acute Malaria, revealing a clear correlation between pro-inflammatory cytokine TNF-α and EBV-DNA levels, specifically in P. falciparum cases, suggesting this cytokine to be key in dysregulating EBV homeostasis during acute P. falciparum Malaria.